Milan Criteria and UCSF Criteria: A Preliminary Comparative Study of Liver Transplantation Outcomes in the United States - Supriya S. Patel; Amanda K. Arrington; Shaun McKenzie; Brian Mailey; Michelle Ding; Wendy Lee; Avo Artinyan; Nicholas Nissen; Steven D. Colquhoun; Joseph Kim (International Journal of Hepatology)
The application of orthotopic liver transplantation (OLT) for patients with hepatocellular cancer (HCC) necessitates highly selective criteria to maximize survival and to optimize allocation of a scarce resource. The objective of this study was to compare the outcomes of OLT for HCC in patients transplanted under Milan and UCSF criteria. The United Network of Organ Sharing (UNOS) database was queried for patients who had undergone OLT for HCC from 2002 to 2007, and 1,972 patients (Milan criteria, n=1,913; UCSF criteria, n=59) were identified. Patients were stratified by pretransplant criteria (Milan versus UCSF), and clinical and pathologic factors and overall survival were compared. There were no differences in age, gender, diabetes mellitus, body mass index, and hepatitis B, or C status between the two groups. Overall survival was similar between the Milan and UCSF cohorts (1-, 2-, 3-, and 4-year survival rates: 88%, 81%, 76%, and 72% versus 91%, 80%, 68% and 51%, respectively, P=0.21). Although the number of patients within UCSF criteria was small, our results nevertheless suggest that patients with HCC may have equivalent survival when transplanted under Milan and UCSF criteria. Long-term followup may better determine whether UCSF criteria should be widely adopted.